The effect of halal tourism quality on economic growth Islamic countries - Fahmy, Edian; Muhammad (CV ODIS, 2024)
This study examines the effect of halal tourism quality on economic growth in countries with the largest Muslim population in the world. This study also examines the role of the level of tourism acceptance as a mediator variable in mediating the effect of halal tourism quality on economic growth. In this study, the quality of halal tourism with the global Muslim travel index (GMTI) was published by Crescenrating. Using 26 countries that are members of the Organization of Islamic Cooperation (OIC) in the period 2016 to 2022, this study found that halal tourism quality has a positive effect on tourism revenue. In addition, halal quality also has a direct positive effect on economic growth. On the other hand, this study did not find a significant role of tourism revenue in mediating the indirect effect of halal tourism quality on economic growth. This study implies the importance of improving the quality of halal tourism in driving economic growth in Muslim-majority countries, especially to compete in attracting more Muslim tourists.